1997
DOI: 10.1006/viro.1997.8782
|View full text |Cite
|
Sign up to set email alerts
|

p53/E1b58kDa Complex Regulates Adenovirus Replication

Abstract: We have explored a role for the adenovirus (Ad5) E1b58kDa/p53 protein complex in adenovirus replication. This was done by using virus mutants containing different defects in the E1b58kDa gene and cell lines that express either a wild-type p53 protein or a mutant p53 protein. We find that infection of wild-type p53-containing cells with wild-type Ad5 causes a shutoff of p53 and alpha-actin protein synthesis by distinct mechanisms, but neither occurs in mutant p53 cells. Our data also indicate that the shutoff i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 45 publications
6
38
0
Order By: Relevance
“…3). The results obtained when U-251 MG cells were infected with both viruses (Ad5¢24 and Ad5CMV-p53) agree with previous reports that p53 can cooperate with other viral and cell proteins to enhance adenovirally mediated cell death (12).…”
Section: Resultssupporting
confidence: 90%
“…3). The results obtained when U-251 MG cells were infected with both viruses (Ad5¢24 and Ad5CMV-p53) agree with previous reports that p53 can cooperate with other viral and cell proteins to enhance adenovirally mediated cell death (12).…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, D24 adenovirus induced cell death even in mutant-p53 cells such as U-251 MG glioma cells (Gomez-Manzano et al, 1996) and Saos-2 (Masuda et al, 1987). These results indicated that although p53 can cooperate with other viral and cell proteins to enhance adenovirallymediated cell death (Ridgway et al, 1997), wild-type p53 status was not a major determinant of ecient D24 replication and thus its oncolytic eect.…”
Section: Treatment With D24 Induces Entry Of Cells Into S Phase and Cmentioning
confidence: 96%
“…4,[6][7][8] However, these studies have produced considerable controversy. Using matched colon cancer cell lines Bischoff et al 4 reported reduced replication of ONYX-015 virus in the p53 transfectant cell line using burst assays as the measure of replication.…”
Section: Resultsmentioning
confidence: 99%
“…5 However, others have investigated the association between ONYX-015 viral replication and p53 status in a variety of cell lines and have reported no association. 6,7 Indeed, Hall et al 8 suggested that ONYX-015 induces cell death more efficiently in wildtype p53 containing cells, thus questioning the proposed selectivity of ONYX-015 for p53 deficient tumour cells. However, this study did not determine whether the mechanism of cell death was due to cytolysis induced by viral replication or virus-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%